Germanistik in Wien Das Seminar für Deutsche Philologie und seine Privatdozentinnen (1897-1933) - Grabenweger, Elisabeth (Quellen und Forschungen zur Literatur- und Kulturgeschichte, 2016)
The series "QUELLEN UND FORSCHUNGEN ZUR LITERATUR- UND KULTURGESCHICHTE" (Sources and Research in the History of Literature and Culture), with a rich tradition stretching back to 1874, is an established feature among the renowned publications for German Literary Studies. Edited by Ernst Osterkamp and Werner Röcke at the Humboldt University of Berlin, the series presents examples of high-quality scholarship examining literary texts in conjunction with historical cultural phenomena, particularly with the other arts. There is an explicit demand for literary studies with a transdisciplinary approach. German literature from the Middle Ages to the present day forms the main focus of the series. As the historical cultural thrust of the series includes aspects of intercultural experience and national perceptions of the other, Quellen und Forschungen is also open to occasional comparative studies. The publications of the series include monographs, doctoral and professorial theses and thematically focused volumes of collected papers. Works presented for acceptance in the series are required to display scholarly relevance and excellence in method and presentation.